A Prototype Model Design of Wide Band Standard Reference Rod-Dipole antenna for 3-Axis EMC Measurement with hybrid Balun for 0.9 to 3.2GHz - S. Patil; P. Petkov; B. Bonev (Advanced Electromagnetics, 2018)
Every electronics equipment must deal with EMC test. The testing laboratory of electronics equipment for radiation emission must have accurate calibrated antennas. The field strength of total radiated radio frequency is average of all incident signals at given point, this incident spinals originates from various directions. In order to measure three components of all electric field vectors, a tripole antenna is most beneficial over conventional antenna because of it responds to signal coming from multi directions. This paper presents novel three axis wide band calculable rod-dipole antenna with hybrid balun for the range of 900MHz to 3.2GHz frequencies, the proposed antenna is small in size and good electrical characteristics, the Important parameters measured and verified with designed values. Return loss S11 more than -10dB within the frequency range 900MHz to 3.2GHz. The result of this articles are evident that, efficient construction of antenna with low cost, light weight module applicable for EMC pre-compliance test at open field site.